Control interno y su incidencia en la gestión de cobranza de la Compañía Transutah S.A., en el cantón Guayaquil - Echeverria Banchon, Jesús Alberto (2021)
Internal control has its importance within any institution, whether it is public, private or mixed, being those that allow results to be given easily and these are efficient and effective, these processes occur in all the areas involved, for our research, it was the starting point to know if this influenced the collection of overdue portfolio of the company under investigation. Recognizing within the investigation that establishing processes developed in conjunction with administration, finances and internal control, help the collection management of a company to be carried out in accordance with its objectives or if it is not met. For this research work, the Financial Management and Social Commitment research sub-lines were used, where through the application of qualitative research, based on tools such as the interview with the accountant and manager of the company and the observation of the elderly accounts receivable, and the application of internal rules or policies that the company has. Discovering that the company does not handle collection techniques or policies, due to the lack of planning and control strategies that allow it to recover the portfolio in a short time, applying empirically the use of procedures to carry out the control of the accounts receivable and application of collection strategies.